Tekanan Kompetisi pada Atlet Remaja Pencak Silat Kategori Tanding: Sebuah Ulasan tentang Pentingnya Peran Orang Tua dan Pelatih - Ardi Setyo Nugroho; Galih Prastyo Utomo; Bambang Purwanto; Sulistiawati Sulistiawati (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2022)
Abstract Physical activity from many studies has proven to have a positive impact on mental health. But also intense physical activity over a long period, induce athletes to feel depressed actually harm mental health. Adolescent athletes have the load of undergoing special training and competition to get high hours of competition. Psychological stresses have an impact on emotional stress associated with intensive training and competition demands, until induce a reduction in athletes' performance abilities and skill levels when competing. Psychological stress be one of induce failure to reach the peak of achievement. Environmental support, especially parents and coaches, play an important role in supporting adolescent athletes learn about self-control over stress (coping). Specific support and strategies, based on the experience provided by parents and coaches, provide valuable positive encouragement for adolescent athletes to deal with psychological stresses during competition. Support from parents and coaches increase protective factors such as optimism, can help athletes deal with psychological stress during competition. This article reviews the competition pressures on adolescent pencak silat athlete in the category tanding, with the perspective of the role of parents and coaches as the main environment of adolescent athletes. See not many scientific articles that discuss the pressure of competition from this point of perspective. Keywords: Psychological stress, Competition, Pencak silat, Coach, Parents